Investigating the Difficulties Faced by Iraqi EFL Students Teachers in the Practicum Teaching Phase - Fanukh Abbas, Chassib (International Journal of Psychosocial Rehabilitation, 2020)
The necessity for more and well-qualified teachers of English in Iraq is greater than ever before, due to the fact that without English proficiency, professionals in mostly all sectors of the community are blocked from career advancement and self-development. Accordingly all difficulties and obstacles that are likely to hinder the promotion of skilled language teacher preparation should be carefully investigated and then treated and terminated. In agreement with the idea that the language teaching profession, like all of education, is faced with accountability issues that call for improved teacher preparation as a means of improving students language learning, the present paper investigates and classifies the different problems faced by EFL student teachers during practicum, aiming at calling attention to these difficulties and their negative impact on EFL teacher preparation, which in turn affects EFL learning all over Iraq. The population of the study consists of student teachers at the Iraqi Colleges of Education/Departments of English during their field experience at schools, while the sample includes student teachers at the College of Education, University of Babylon/Department of English during the academic year 2016–2017. They were (128) student teachers practicing their practicum teaching at different intermediate and secondary schools in Babylon. The results of the study proved that student teachers at the departments of English of the colleges of education in general do face real problems that are related to different categories. And that these problems affect the teaching performance of student teachers during practicum. In light of the study findings, a set of remedial recommendations is presented.